NITRATE-RICH BEETROOT JUICE ALONE OR IN COMBINATION WITH FOLIC ACID REDUCES BLOOD PRESSURE IN HYPERTENSIVE TANZANIAN ADULTS: A DOUBLE-BLIND RANDOMIZED CONTROLLED TRIAL. (April 2021) - Prabhakar, Meghna; Kandhari, Navneet; Shannon, Oliver; Fostier, William; Koehl, Christina; Rogathi, Jane; Temu, Gloria; Stephan, Blossam; Gray, William; Paddick, Stella Maria; Haule, Irene; Mmbaga, Blandina; et al.
Abstract : Objective: In Sub-Saharan Africa, current management strategies are struggling to control the burgeoning hypertension epidemic. Dietary interventions such as inorganic nitrate and folate could represent alternative strategies for reducing blood pressure in this setting. This study aims to explore the effects of dietary inorganic nitrate supplementation alone or in combination with folic acid supplementation on blood pressure in a group of adult individuals with elevated blood pressure in Tanzania. Design and method: A placebo-controlled, double blind, randomized controlled trial (RCT) was conducted. Forty seven participants were randomly assigned to three conditions for a period of 60 days: 1) high-nitrate beetroot juice (∼400 mg nitrate) and folic acid (∼5 mg folate), 2) high-nitrate beetroot juice and placebo, 3) nitrate-depleted beetroot juice and placebo. Clinic and 24-hour ambulatory blood pressure, markers of nitric oxide production, and measurements of intervention compliance were obtained prior to and following the intervention period. Results: Resting clinic-based systolic blood pressure was significantly lower after 60 days of nitrate supplementation alone (p = 0.01). Both alone and combined nitrate + folate interventions had a significant effect on 24-Hour systolic blood pressure. After 60 days systolic blood pressure dropped by −10.8 ± 9.8 mmHg (p < 0.001) and −6.1 ± 13.2 mmHg (p = 0.03) in the nitrate alone and nitrate + folate groups, respectively. There was a significant decrease in 24-hour diastolic blood pressure in the nitrate alone group (−5.4 ± 5.0 mmHg, p = 0.04). Conclusions: Dietary inorganic nitrate, alone or in combination with folic acid, represents a potential nutritional strategy to lessen the hypertension epidemic in Sub-Saharan Africa. These findings support the rationale for future long-term investigations exploring the efficacy of dietary nitrate for lowering blood pressure and attenuating CVD risk in this setting.